The Analysis of Quality Information on The Website of South Bengkulu, Bengkulu Province - Sussy Nofita Sari; Desak Made Trisna Juliantari Dewi; Nyoman Diah Utari Dewi (Indonesian Association for Public Administration (IAPA), 2022)
The information and communication technology (ICT) development today has created a website, an effective information medium that connects to the Internet network so that it can be accessed at any time. Not want to miss, government organizations are also utilizing website technology as one of their services in providing information to the public. However, the information contained on the website should have a good quality so that the information conveyed can be useful. This study aims to measure the quality of information on South Bengkulu Regency websites based on dimensions of the information quality concept. Observation of four websites in South Bengkulu Regency was conducted along with an in-depth interview with each manager. The results obtained that the information available on these websites has met the good information quality, although there are some deficiencies such as the existence of links that refer to a blank page, some unlisted information dating, and the lack of network quality assurance to ensure the availability of information.